A Conceptual Model of a Mobile Application to Support Paralyzed Stroke Patient Care at Home - Iustina-Cristina Costea-Marcu; Gheorghe Militaru; Cristina-Petronela Simion; Corina-Ionela Dumitrescu (Communications of International Proceedings, 2020)
There are a lot of people that after having suffered a cerebrovascular accident (CVA) remain incapacitated and bed bound, presenting different types of plegia. These people require constant assistance from either a relative or a special care worker. This paper proposes an application that will aid those who assume the responsibility of taking care of a paralyzed person that just went through a CVA. The caretaker will have access to information pertaining to different categories – both medical and therapeutical, but also information regarding the rights and facilities of those diagnosed with different forms of plegia. Moreover, in some cases the caretaker may request further information or even ask for a consult that will be given at the patient’s location. This leads to having the great advantage of avoiding superfluous calls to the National Ambulance Service. The chosen methodology uses indirect research for the references study and direct research through interviews with people that have taken care of paralyzed CVA patients.
Keywords: Medical Application; Healthcare; Stroke; Homecare; Plegia.